Ketercapaian Indikator Keberdayaan Masyarakat dalam Program Pemberdayaan Fakir Miskin (P2FM) di Kota Banjarmasin - Hairi Firmansyah (Universitas Lambung Mangkurat, 2012)
The purpose of this study was to analyze the achievement of empowerment indicators (degree and empowerment bases ) Fakir's of poor Empowerment Program (P2FM). This study was a survey research. Respondents of this study amounted to 30 people taken to the sample multistage random sampling techniques (stratified simple random). The sample were subjected to community members or beneficiaries the Fakir's of poor Empowerment Program (P2FM) in the helder Banjarmasin City. The results showed that the achievement of empowerment indicators (degree and empowerment bases) on the Fakir's of poor Empowerment Program (P2FM) which was conducted in the Banjarmasin City not able to empower the target communities or beneficiaries of the program, so not worth mentioning as the community empowerment program.